Efeitos de uma capacitação sobre envolvimento familiar para estagiários em fisioterapia neuropediátrica - Gennaro, Lisandrea Rodrigues Menegasso (2012)
The research literature indicates that the relationship between physiotherapists and family caregivers of children with neurological disorders has a significant impact on the efficacy of the children s treatment. However, the fragmentation of knowledge and the tendency to over-specialize can result in the preparation of professionals who understand organic pathology and treatment techniques, but who lack skills to deal with the interpersonal and educational issues that underlie their relationship with the children s family caregivers. In addition, very few researchers have published studies analyzing the effectiveness of strategies that physiotherapists could be used to increase the involvement of family caregivers. As such, the objectives of the current research program were to: a) identify physiotherapy practicum students conceptions about (Study1) and abilities (Study 2) to involve a child s family member in the treatment process, and b) evaluate an intervention program that was designed to increase the students abilities to involve family caregivers in this process (Study 3). The research program was conducted with physiotherapy practicum students from a high-caliber course, who were working in a university clinic. Study 1 was conducted with 10 students, using semi-structured interviews. The students recognized the importance of including a family member in the treatment of children, but they perceived their preparation to deal with this family member as being insufficient. In Study 2, seven students were filmed when they were in the presence of the caregivers, over the course of four weeks. In 34 of the 73 film segments (46.5%), the students did not interact with the family caregivers. The students spoke with the caregivers in 26 film segments (33%), primarily to initiate and maintain a conversation (n = 18) or to ask questions (n = 9). Thus, the results of Studies 1 and 2 indicated the need for an intervention program for this population. In Study 3, such a training program was evaluated. The eight-hour program aimed to teach basic skills related to behavior analysis, family-centered practices, and social skills. Participants included 5 practicum students. Each training program session included a pre-test on the concepts that were to be learned, a teaching segment to explain these concepts, interactive tasks, practice exercises and a post-test. Based on a comparison of the results on the pre and post-tests, it was apparent that the students acquired new knowledge during the program. A comparison of film segments recorded at the beginning and the end of the training program indicated that the students increased their use of the following strategies to involve the children s family caregivers: provide feedback, ask for assistance with an exercise, offer praise, converse, and ask questions. In addition, the film segments for the group of students who completed the intervention program (IG), were compared with the film segments from Study 2, using these students as a comparison group (CG). The behavior of both groups in the initial film segments was highly similar, but, one month later, the ability of the IG students to involve the caregivers was greater than that of the CG students. Thus, the results indicate that the intervention was effective. As such, it would be important to continue applying this intervention so as to evaluate the effects for a larger number of participants, and to conduct a follow-up study to verify the permanency of the behaviors that are acquired. In conclusion, this research program constitutes an example of an interdisciplinary approach to the training of physiotherapists, aligned with the philosophy of a universal health system, aiming for a holistic approach and excellence in caring for children with neurological disorders and for their families.